1985
DOI: 10.1002/bip.360241205
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of blood group H‐active oligosacharides of ovarian cyst mucins

Abstract: SynopsisSpectroscopic data and conformational energy calculations are reported for eight oligosaccharides from ovarian cyst mucins and from human milk, the nonreducing terminals of which have fucose (a1 -2)galactose linked either (Pl-3) (type I) or (pl-4)(type 11) to Nacetylglucosamine or in ( D l -3 ) linkage to galactosaminitol. The fully assigned proton nmr spectra are reported along with nuclear Overhauser enhancement (NOE) data. Amide proton coupling constants and vacuum-uv CD spectra provide information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 27 publications
(3 reference statements)
5
13
0
Order By: Relevance
“…LSIMS of the permethylation product MH' m/z 1176 and the partially methylated alditol acetates (Table 2) were consistent with this interpretation, the latter clearly showing the GalNAc(1 -) and (-2,3)Gal(l -) features. (Table 8) matched previously recorded data [23,24,26] for a hexasaccharide having a terminal bloodgroup-H determinant on both arms. Its permethylated LSIMS MH' ion at m/z 1309 and intense fragment ions m/z 638/606, together with methylation analysis (Table 2), were in accord with this assignment.…”
Section: Oligosaccharides Having a Glcnac(b1-6)[gal(bl-3)]-galnacol Csupporting
confidence: 85%
See 1 more Smart Citation
“…LSIMS of the permethylation product MH' m/z 1176 and the partially methylated alditol acetates (Table 2) were consistent with this interpretation, the latter clearly showing the GalNAc(1 -) and (-2,3)Gal(l -) features. (Table 8) matched previously recorded data [23,24,26] for a hexasaccharide having a terminal bloodgroup-H determinant on both arms. Its permethylated LSIMS MH' ion at m/z 1309 and intense fragment ions m/z 638/606, together with methylation analysis (Table 2), were in accord with this assignment.…”
Section: Oligosaccharides Having a Glcnac(b1-6)[gal(bl-3)]-galnacol Csupporting
confidence: 85%
“…The trisaccharide core structure GlcNAc(/YI -6)[Gal(/31-3)]GalNAcol (fractions N2-5/N3-4) and its analogue fucosylated at C2 of galactose on the (2-3 branch (fractions N2-6jN3-5) were identified by Tsuji and Osawa [lo] and have been characterised previously from other sources by 'H-NMR [18,20,[22][23][24][25]. Their structures were fully established in the present study (Tables 1, 2 and 8).…”
Section: Oligosaccharides Having a Glcnac(b1-6)[gal(bl-3)]-galnacol Cmentioning
confidence: 99%
“…However, this may not be true for branches linked to GalNAcr-SerlThr rather than GalNAcol. The proposed spatial orientation of the periphcral substitutions, GlcNAcml-4 linked to Galpl-4GlcNAcfil-6 in fractions K2(3), K4(2), and K6(3) and Fucal-2 linked to Galpl3GalNAcol in fraction K6(3), suggest that these form relatively globular conformational domains as has been shown for the blood group and related antigens, H, A, B, Lea, Leh, SSEA-1 and their sialylated analogues [lX, 19,22,[28][29][30][31]. This, together with the possible restricted distribution of thc C?lcNAcnl-4Gal sequence and its relative abundance in human foetal gastrointestinal mucins, suggests its potential as an epithelial marker for differentiation stage and neoplastic transformation.…”
Section: Dtscussionmentioning
confidence: 81%
“…As discussed above for oligosaccharide K2(3), the H4 rcsonance of GalNAcol is particularly susceptible to changes in shielding depending on the substituent on Gal linked pl-3 to it. This, together with the identification of chemical shifts characteristic of a GlcNAcal4GlcNAcfll-6 branch (discussed above) and those for fucose linked a1-2 to Gal in p1-3 linkage to GalNAcol [14,[22][23][24] gave the assignment shown in Tablcs 2 and 7 for the major component of fraction K6(3).…”
Section: Oligosaccharicle Fractioii K 4 ( 2 )mentioning
confidence: 99%
“…1 and Table 1 show that lactose-N-tetraose and lactose-N-neotetraose are separated by 8.4 min. Assuming a greater acidity for the 3-OH of GlcNAc relative to the 4-OH, we expected that compound 4 would be a more acidic oligosaccharide and, therefore, elute after compound 5. Conformational analysis of these two types of linkages showed that the disaccharide unit, Gal(,81-3)GlcNAc, has a distinct hydrophilic face produced by both monosaccharides (33,34). In contrast for Gal(1-4)GlcNAc, the hydroxyl groups of galactose and GlcNAc are in distinct planes and do not form a "sheet" of hydrophilic residues.…”
mentioning
confidence: 99%